2011
DOI: 10.1038/mp.2011.75
|View full text |Cite
|
Sign up to set email alerts
|

Disambiguating ventral striatum fMRI-related bold signal during reward prediction in schizophrenia

Abstract: Reward detection, surprise detection and prediction-error signaling have all been proposed as roles for the ventral striatum (vStr). Previous neuroimaging studies of striatal function in schizophrenia have found attenuated neural responses to reward-related prediction errors; however, as prediction errors represent a discrepancy in mesolimbic neural activity between expected and actual events, it is critical to examine responses to both expected and unexpected rewards (URs) in conjunction with expected and UR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
121
7

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(142 citation statements)
references
References 49 publications
(78 reference statements)
14
121
7
Order By: Relevance
“…25,26 In contrast, the current study investigated a psychosis continuum from nonclinical participants to patients with early psychosis with a different psychopathological construct of apathy (partly secondary to positive and depressive symptoms). Furthermore, our results are consistent with findings of Morris and colleagues 53 who found the same relationship of exaggerated VS activity with negative symptoms and total symptom severity suggesting a more complex picture between aberrant ventral striatal activity and psychopathology.…”
Section: Discussionsupporting
confidence: 93%
“…25,26 In contrast, the current study investigated a psychosis continuum from nonclinical participants to patients with early psychosis with a different psychopathological construct of apathy (partly secondary to positive and depressive symptoms). Furthermore, our results are consistent with findings of Morris and colleagues 53 who found the same relationship of exaggerated VS activity with negative symptoms and total symptom severity suggesting a more complex picture between aberrant ventral striatal activity and psychopathology.…”
Section: Discussionsupporting
confidence: 93%
“…However, it remains to be determined to what extent the decrement of these responses in latent inhibition or extinction similarly requires opioid activation. It is also worth noting that these results are consistent with the suggestion that the inability to ignore irrelevant stimuli, which characterizes positive symptoms in schizophrenia, may originate from dysfunctions in error-correction learning (eg, Corlett et al, 2007;Morris et al, 2012). The sensitivity of this learning to naloxone implicates endogenous opioids as a potential pharmacological target for the treatment of schizophrenia, and is consistent with post-mortem analysis showing alterations in cortical opioid receptors in the brains of schizophrenics (Volk et al, 2012).…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, these regions are key components of the reward network (McClure et al, 2004;Sesack and Grace, 2010). We and other have reported on changes in frontostriatal reward processing in schizophrenia patients (Morris et al, 2012;Nielsen et al, 2012), siblings (Grimm et al, 2014;de Leeuw et al, 2015b), and offspring (Vink et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, neuroimaging studies have consistently shown frontostriatal impairments in schizophrenia patients. First, functional MRI studies have demonstrated reduced levels of frontostriatal activation in patients in the context of several cognitive tasks including working memory, reward processing, and inhibition (Morris et al, 2012;van Veelen et al, 2010van Veelen et al, , 2011Vink et al, 2006;Zandbelt et al, 2011). Second, patients show decreased frontal and striatal volumes (Emsley et al, 2015;Harms et al, 2010).…”
Section: Introductionmentioning
confidence: 99%